Analisis Nilai Tambah untuk Meningkatkan Keberlanjutan Rantai Pasok Agroindustri Kopi di Kabupaten Kerinci - Heppi Syofya (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
The purpose of the research is to analyze the amount of added value obtained by the actors and design a proposed strategy to increase the sustainability index in the coffee agro-industry supply chain. The analysis of added value was carried out using Hayami. The stages carried out were conversion analysis, identification of actors involved in the supply chain and calculating the profits of each actor. The amount of profit obtained by the actors in the existing supply chain is quite diverse, where the largest profit is obtained by KUB (80.42%), while the smallest profit is obtained by farmers, namely 56.96%.